FAKTOR YANG MEMPENGARUHI TINGKAT PENGEMBALIAN PINJAMAN PADA USAHA EKONOMI DESA SIMPAN PINJAM (UED-SP) DI KABUPATEN INDRAGIRI HULU - Eko Purwanto (JIAGANIS, 2018)
Abstract: factors that affect the rate of return on loans in the savings and loan village economic businees (UED-SP) in District Indragiri Hulu. This research is to analyzing  thefactors that affect the rate of return on loans in the savings and loan village economic businees which causes low loan repayment rates.This research uses a quantitative approach. Data collection through documentation and questionnaires. Data analysis techniques are regresision equations, Multicollinearity Test,Autocorrelation Test, Heterokedasticity Test, Hypotesis Test, Overall Test, Determination Test. Based on the research results, it is known that by using a statistical tes the results stated that of the six factors studied (internal factors), where is the factors giving and supervising deviant credit (X5) significantly affects the level of loan repayments (Y) in District Indragiri Hulu. Simultaneously showing that factor where is the factors giving and supervising deviant credit (X5) significant effect on the dependent variable loan repayment rate (Y) this is indicated by the value thitung >  ttabelon significant level α = 0,05,  value nilai Fhitung >  Ftabeland the magnitude of the influence contributed by independent variable to the dependen variable is seen from determination  (R2), while closeness the relationship can be seen from coefficien efficient R, this is indicsted by the coefficient value 0,906 which is the biggest factor compared to other factors.Keywords: Loan Repayment; UED-SP.